Diversity of Microfungi in Litter of Pine Forests in Duhok - NASHAT, LAVA HIKMAT; ABDULLAH, SAMIR KHALAF (Science Journal of University of Zakho, 2013)
The litter microfungi of Pine forests located in Zawita and Atrush were studied with objective to compare the composition, frequency of occurrence and diversity of fungi in forest habitats from Duhok, Kurdistan region of Iraq. A total of 11 species in addition to sterile mycelia were identified from L1 litter layer from the two sites, whereas, 9 species were identified from L2 layer at both sites. In general, the detected species from both litter layers (L1,L2) at the two sites included: Aspergillus flavus, A.fumigatus, A.niger, Alternaria alternata, Aurobasidium pullulans, Cladosporium cladosporoides, C.gallicola, Fusarium sp., Papulaspora pallidulla, Penicillium glabrum, Rhizopus sp. Scytalidium lignicola,Ulocladium atrum in addition to non-sporulating mycelia. Of these A.pullulans was the most frequent species on freshly and decomposed pine needles litter at the two sites. The least (SI) index for fungal community inhabiting Pine litter was recorded between L1 and L2 layers at Zawita. Whereas, the highest (SI) was found between L1 layer at Atrush and L2 layer at Zawita site. Papulaspora pallidulla represents a first record for Iraqi mycobiota. Brief description along with photographs are provided for the newly reported species.